IN SEARCH OF STRATEGIES USED BY PRIMARY SCHOOL PUPILS FOR DEVELOPING FRACTION SENSE (Malaysian Journal of Learning and Instruction, 2020)
Purpose â€“ Most literature has focused solely on either knowledge about number sense or understanding of fractions. To fill the research gap, this study examined pupilsâ€™ abilities in both number sense and fractions. In particular, it investigated Year 4 and Year 5 pupilsâ€™ use of strategies in developing their fraction sense. Methodology â€“ This study adopted a descriptive research design, utilising a mixed approach in data collection. An instrument called the Fraction Sense Test (FST) and a clinical interview were used to collect data. The FST comprised 3 strands: fraction concept, fraction representation and effect of operation. A two-stage cluster sampling method was employed to select 396 Year 4 and Year 5 pupils. The sampling involved random selection of the primary schools in the first stage, followed by pupils within the selected schools in the second stage. In addition to descriptive statistics, content analysis of interview transcripts was conducted to identify the presence of concepts and strategies applied among the pupils. Findings â€“ The study found that the pupils scored lowest in effect of operation. It was also revealed that there were four strategies which helped the pupils to develop fraction sense, namely (1) comparing fractions using benchmark fractions of common fractions such as Â½, Â¼, zero and 1, (2) understanding denominators to determine the size of equal parts, (3) comparing fractions using unit fraction, and (4) applying the strategies in (1) and (2) to manipulate fractions in effect of operation. Significance â€“ The findings provide useful input to facilitate the development of fraction sense ability.